The political and social dimension of covenants and security pacts in the Abbasid era (170-218 AH / 786-833 AD) (Journal of the College of Basic Education, 2022)
Covenants and security charters are of great importance to Muslims, as they had a profound impact on their lives, as they strengthen their being, give strength to their personality, and guarantee their future against the ravages of time.Man sees with his insight how God’s Sunnah operates in societies without favoritism or injustice, how states rise and fall, how calls triumph and are defeated, how leaders succeed and fail, and so on during the Abbasid Caliphate era, especially in the era of the Rashid Caliph (170-193 AH) (786-808 AD) nature led The political circumstances accompanying the emergence of the mandate of the Covenant and the consequent giving of pledges of safety by the Crown Princes and a group of opponents who appeared on the political and military arena, the Abbasid Caliphate confronted these opposition movements strongly. This led Caliph Al-Rashid (170-193 AH 786-808 AD) to conclude agreements and negotiate with the leaders of these movements.